Sustainable Tourism for the Green Economy - Nataliia Letunovska; Aleksy Kwilinski; Henryk Dzwigol; Oleksii Lyulyov; Tetyana Pimonenko (Virtual Economics, 2021)
The paper analyses the innovative direction of sustainable tourism in Poland. It is investigated by means of a marketing survey of the respondents from this country and neighbouring regions. The authors’ findings deal with the results in the framework of the green economy. The research hypothesis is to check the target group’s awareness of post-industrial tourism in the field of region's rehabilitation, readiness to support sustainable development goals in their areas and to determine the most effective marketing tools to promote sustainable tourism. The authors found that local authorities play an essential role in developing territories through implementing healthy regional strategies. Among the insights of the research is the concept of Smart City as a promising tool for promoting healthy types of activity, to the respondents' opinion. Regions are defined as local centres where sustainable tourism principles could be implemented to reduce consequences unwelcome for the environment and economy.